Produksi Etanol Berbahan Baku Molasses Melalui Proses Fermentasi Menggunakan Ragi Roti - Yustia Wulandari Mirzayanti; Sugiono .; Reta Kurniayati (Institut Teknologi Adhi Tama Surabaya, 2021)
One of the alternatives and renewable energy that is being developed is ethanol.Ethanol is better known as Gasohol. Molasses can make Gasohol through thesynthesis of molasses fermentation using a yeast starter. This study aims toanalyze how the effect of the addition of baker's yeast, the length of fermentationincubation time on the resulting alcohol content. In addition, the yield obtainedfrom the highest amount of ethanol production in the molasses fermentationprocess. Ethanol production through fermentation synthesis using the help ofmicroorganisms Saccharomyces cerevisiae. Based on the objective review, thevariation used is the amount of baker's yeast, namely 0.1; 0.2; 0.3; 0.4; and 0.5%glucose levels. The fermentation times were 24, 48, 72, 96, and 120 hours (T =30?C and pH = 5). Based on these variations, the highest alcohol productionwas 11%, obtained by adding 0.2% of yeast to the glucose content in the solution.The incubation time is 72 hours. The yield obtained for the highest alcoholcontent is 4.48%